The Role of Trust and Financial Literacy on Intention to Use Services Buy-Now-Pay-Later with Approach Extended Theory of Planned Behavior Model - Florencia Irena, Bernadette; Amalyah Agus, Anna (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The Buy Now Pay Later (BNPL) service is a fintech innovation that allows consumers to purchase with delayed payments. Its popularity is increasing with the growth of e-commerce and the need for flexible payments, but understanding the factors that influence usage intentions remains limited. This research analyzes the influence of trust and financial literacy on intentions to use BNPL in Indonesia using an approach to the Extended Theory of Planned Behavior. The study was conducted quantitatively on 405 respondents and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM), including Multigroup Analysis (MGA) based on gender and financial literacy level. The results show that trust significantly affects attitudes and intentions to use BNPL. In contrast, financial literacy does not directly impact intentions but influences attitudes, beliefs, and perceived behavioral control. Multigroup analysis shows that subjective norms are more influential on women's intentions, and privacy concern influences attitudes more in individuals with low financial literacy. These findings emphasize the importance of building trust and increasing financial literacy to encourage the wise use of BNPL. Practical implications are aimed at industry players and regulators in designing educational strategies and consumer protection policies.